2014
DOI: 10.1021/la500510s
|View full text |Cite
|
Sign up to set email alerts
|

Push–Pull Mechanism for Lipid Raft Formation

Abstract: A quantitative assessment has been made of the interaction between exchangeable mimics of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and cholesterol in the liquid-ordered (l0) and the liquid-disordered (ld) states using the nearest-neighbor recognition (NNR) method. This assessment has established that these lipids mix ideally in the l0 phase (i.e., they show no net attraction or repulsion toward each other) but exhibit repulsive interactions in the ld phase. The implications of these findings for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 30 publications
4
61
0
Order By: Relevance
“…The highest profile is DPPC-POPC in the l d phase, suggesting that interactions between saturated phospholipids and monounsaturated phospholipids in the l d phase are most unfavorable, which is consistent with the push force measured by Regen et al 8 The resulting PMF for the pairs involving cholesterol are shown in Figure 3b. In 6 Å < r < 10 Å, there is a clear minimum for CHOL-DPPC in the l o phase compared to the other cholesterollipid interactions, which corresponds to the strong pull proposed by Regen et al 8 The interactions for CHOL-POPC in either the l d phase or the l o phase are clearly unfavorable with respect to the strong pull of CHOL-DPPC in the l o phase, which can be attributed to the significant push between cholesterol and monounsaturated phospholipids 3,8 . In contract to the other interactions, the PMF for CHOL-CHOL has several local minima keeping the same positions in the l d phase and the l o phase, which indicates that the favorable packing distances among cholesterol are not affected by the phases.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The highest profile is DPPC-POPC in the l d phase, suggesting that interactions between saturated phospholipids and monounsaturated phospholipids in the l d phase are most unfavorable, which is consistent with the push force measured by Regen et al 8 The resulting PMF for the pairs involving cholesterol are shown in Figure 3b. In 6 Å < r < 10 Å, there is a clear minimum for CHOL-DPPC in the l o phase compared to the other cholesterollipid interactions, which corresponds to the strong pull proposed by Regen et al 8 The interactions for CHOL-POPC in either the l d phase or the l o phase are clearly unfavorable with respect to the strong pull of CHOL-DPPC in the l o phase, which can be attributed to the significant push between cholesterol and monounsaturated phospholipids 3,8 . In contract to the other interactions, the PMF for CHOL-CHOL has several local minima keeping the same positions in the l d phase and the l o phase, which indicates that the favorable packing distances among cholesterol are not affected by the phases.…”
Section: Resultsmentioning
confidence: 54%
“…Mixtures of phospholipids and cholesterol form liquid-disordered (l d ) and liquid-ordered (l o ) phases at different cholesterol concentrations. While the l o state has been considered as a good working model for lipid rafts, the l d state mimics well the fluid, liquid crystalline phase of lipid membranes 3,4 . Study of the interactions of lipid-lipid and cholesterollipid in both l d and l o phases is important for further understanding of cell membranes 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In a nonideal mixture of low-and high-melting glycerophospholipids, cholesterol associates preferentially with the high-melting, saturated lipids. 4 Cholesterol and the glycerophospholipids interact strongly but transiently 5 via (i) hydrogen bonds between the hydroxy group of cholesterol and the phospholipid phosphodiester, 6 (ii) hydrogen bonds among the hydroxy group of cholesterol, water, and the sn-1 carbonyl moiety of the phospholipid, 7 (iii) van der Waals hydrophobic forces between the planar cholesterol ring system and the sn-1 chain of the phospholipid, 8 and, most importantly, (iv) van der Waals forces between the fatty acyl chains and the cholesterol side chain. 9 The interactions are strongly dependent on the type of phospholipid headgroup and lipid tail saturation 10 and may lead to a positioning of cholesterol in the middle of the bilayer membrane in the presence of polyunsaturated phospholipids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cholesterol prefers the liquid ordered phase rather than the liquid disordered phase [21,22]. Inclusion of fatty acids and diacylglycerols induces ordering in lipid bilayers, rather than homogeneous mixing [23].…”
Section: Discussionmentioning
confidence: 99%